If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -2lx + -4l + 2 Reorder the terms: y = 2 + -4l + -2lx Solving y = 2 + -4l + -2lx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 2 + -4l + -2lx
| 4y-3*(20-y)=6y-7*(11-y)-1 | | 13=.01x^2-x+30 | | 3x=(4x-3) | | 2(-6x+9)=30 | | 49x^4-1=0 | | P=2(x-y^2)+8 | | -32+x=2(7x-3) | | 15b+9= | | 4x+13=-29 | | 8x-70=2x | | (1x)(1y)(.5)=75 | | 7.6x-2.3=95.4 | | 21+7(x-3)=6x+5 | | 9x-2=27x+10 | | (x-3)(2x-6)=0 | | -0.5*32x^2+80x+0=96 | | -12(p+4)=60 | | 360=(x-5)+(x+35)+1.4x+x | | ex^3-8x=182 | | 5(6x+12)=5 | | 7(-2x+5)=-7x-14 | | 3(2x-8)-2x=16 | | 7(5x+23)=5 | | 19(p+6)= | | 4x-4=x-34 | | 6.7x-4.8x= | | 11-r=12 | | -43+y=-45 | | 1=g-4 | | -2x-16=-4x+12 | | 6(8+x)=84 | | 72+8y=208 |